IMPLEMENTASI METODE TOPSIS PADA SISTEM PENDUKUNG KEPUTUSAN SELEKSI PEMBERIAN PINJAMAN BADAN USAHA MILIK DESA (STUDI KASUS : DESA BATU NAMPAR INDUK) - Rika Nurhaliza; Maulana Ashari; Wafiah Murniati; Sofiansyah Fadli (Pusat Riset dan Inovasi Nasional, 2022)
The selection process for granting loans to BUMDes Sinar Linus is done conventionally, in this case it makes researchers feel interested in designing a WEB-based Decision Support System as a decision support tool for members of BUMDes Sinar Linus. The methodology used in the development of this system is a method of collecting data in the form of observation, interviews and literature study. While the analytical method used is the TOPSIS (Technique For Others Reference by Similarity to Ideal Solution) method as a decision-making method for the design method using Extreme Programming (XP) which includes planning, design, coding and testing stages. And for the testing method using Blackbox Testing includes home display, login, loan application, applicant, criteria, alternative and TOPSIS. This research resulted in a web-based decision support system that can facilitate members of the BUMDes Sinar Linus in Batunampar Village in deciding or determining prospective recipients of loan funds at BUMDes Sinar Linus.